Primary care patients' and providers' perspectives about an online weight management program integrated with population health management: Post-intervention qualitative results from the PROPS study - Ronen Rozenblum; Barbara A. De La Cruz; Nyryan V. Nolido; Saffiya McNulty; Katherine D. McManus; Florencia Halperin; Jason P. Block; David W. Bates; Heather J. Baer (Elsevier, 2022)
Objective: To assess patients' and providers' attitudes about the online weight management program and population health management approach in the PROPS Study, which examined the effectiveness of these strategies in primary care. Methods: We conducted semi-structured interviews with 22 patients and nine providers. Using thematic analysis, we analyzed transcripts of the interviews to identify key themes. Results: Most patients found the online program to be well-structured and easy to use, although a few noted that the information was overwhelming or could be more personalized. Patients mentioned that the support from the population health managers was critical for their success, and several reported that they would have liked more involvement from their primary care provider or a dietitian. Providers also were satisfied with the interventions, and several stated that the population health management support was helpful because it added accountability. Providers suggested that the interventions could be improved by tailoring the information and integrating the online program with the electronic health record. Conclusion: Most patients and providers were satisfied with the interventions, with several recommendations for improvements. Innovation: These findings give additional information about patients' and providers' experience with this innovative approach for managing overweight and obesity in primary care.